Key Decision‐Making in Post‐Failed Internal Fixation of Intertrochanteric Fractures Hip Arthroplasty: A Multicenter Retrospective Study on Fracture Healing's Impact on Femoral Component Selection - Jiexin Huang; Jiagu Huang; Haiqi Ding; Jianhua Lyu; Changyu Huang; Yang Chen; Qijin Wang; Hongyan Li; Baijian Wu; Ying Huang; Minghui Yang; Xinyu Fang; et al. (Orthopaedic Surgery)
ABSTRACT Purpose Following failed internal fixation of intertrochanteric fractures (FIF‐ITF), the decision to use a long‐stem or standard‐stem femoral implant in hip arthroplasty is still debated. This study aimed to explore how the healing status of fractures after FIF‐ITF failure affects the choice of femoral stem and clinical outcomes. Methods Our retrospective cohort study reviewed 105 cases of patients with FIF‐ITF who underwent hip arthroplasty at three tertiary Grade A hospitals between December 2012 and December 2022. We compared the clinical outcomes between patients with healed and unhealed fractures, focusing on the selection of femoral stems in relation to proximal medial support and the healing status of the greater trochanter. The primary outcomes measured were functional results, operative time, blood loss, and incidence of complications. A subgroup analysis was conducted to further evaluate the influence of the proximal medial buttress and greater trochanteric healing on femoral stem selection. Statistical analysis included binary and ordinal logistic regression to identify factors influencing the choice of femoral stems. Additionally, a decision tree model was developed to visually represent and explore the relationship between fracture healing status and the selection of femoral components. Results The study included 38 patients with healed fractures and 67 patients with unhealed fractures. Patients in the healed group predominantly chose standard stems and experienced better functional outcomes (p < 0.001, p = 0.002). In contrast, the unhealed group preferred long stems, resulting in longer surgical durations and increased blood loss (p = 0.008, p < 0.001). Binary logistic regression analysis revealed that nonunion of the proximal femoral medial buttress was an independent risk factor for long stems (p < 0.0001, OR = 10.402). Conclusion The selection of femoral prostheses following FIF‐ITF is influenced by the fracture healing status, particularly the presence of proximal femoral medial buttress. The decision tree model suggested that long‐stem prostheses are more appropriate when there is inadequate fracture healing and the proximal femoral medial buttress is absent.